Factor Analysis of Contraceptive Use of Operative Methods in Men - Vivi Yanti; Gema Asiani; Arie Wahyudi (STIKes Al-Ma'arif Baturaja, 2025)
Male surgical method contraception is the closure of the sperm ducts to prevent pregnancy and is included in the long-term contraceptive method. The purpose of this study was to find out the description and information about the use of contraceptive methods of male surgery. The research design used quantitative and qualitative methods. The quantitative method involves analytical observational research with a cross-sectional design. The study sample amounted to 100 respondents with stratified random sampling technique. Qualitative methods in analyzing by collecting data, presenting data, reducing data and verifying data. Qualitative samples involved 8 informants. The results showed no relationship between age (p-value 0.098), number of children (p-value 0.622), occupation (p-value 0.484), knowledge (p-value 0.883), family support (p-value 0.447, the role of contraceptive extension workers (p-value 0.358), and the availability of health resources (p-value 0.791) with the use of male surgical methods. The results of the qualitative study showed a lack of knowledge and socialization as the main factors in the use of male surgical method contraception has not reached the target. The researcher concluded that there was no relationship between age, number of children, occupation, knowledge, family support, the role of contraceptive field extension workers and the availability of health resources with the use of male surgical method contraception. There needs to be education to increase the use of male surgical method contraception and there is an active effort from officers in providing information to couples of childbearing age, especially those who do not want to have more children, as well as education to wives to support their husbands to use male surgical method contraception.